Development and Simulation of PID-Controller Fuel Cell System with DC-DC Boost Converter - Marghani Assia; Rerhrhaye Fathallah; Ennaciri Yassine; Bouguanssa Issam; El Ayachi Chater; El Akkary Ahmed; Sefiani Nacer (EPJ Web of Conferences, 2025)
In the context of the global shift towards sustainable energy, fuel cells have emerged as a promising technology due to their high efficiency and low environmental impact. Integrating fuel cells into energy systems necessitates effective management of their output, often achieved through DC-DC boost converters. This paper presents a comprehensive study of fuel cell applications, focusing on dynamic modeling, and the integration of a boost converter using a PID-controller PWM strategy. Key components, such as the fuel cell model, boost converter, and control algorithms, are analyzed to enhance system efficiency and reliability. Results from simulations demonstrate the effectiveness of the proposed control strategy in optimizing power delivery from fuel cells to various loads.